Remarks on using tools with truncated edges in the Lublin-Volhynian culture on the example of materials from site no. 7 in Las Stocki, Puławy County - Mączyński, Piotr (Analecta Archaeologica Ressoviensia, 2019)
This article tackles the issue of the use of truncations by the population of the Lublin-Volhynian culture. The corpus of sources for their analyses is a group of 27 tools discovered during the research of the Las Stocki settlement, site 7. Microscopic observa-tion made it possible to separate a considerable group of artefacts bearing use-wear traces on their surfaces. The most numerous were items used for processing plant material and wood. Other activities, like processing stone/pottery, hide, and other unspeci-fied materials were recorded sporadically. Another research problem was the attempt to reconstruct the biographies of the stone tools. The analyses indicated that the materials were only partly useful in the research. This was caused by the poor preservation state of the artefacts and of the recorded use-wear traces. Tackling this issue gave the best results in the case of items used for cutting siliceous plants, which undoubtedly resulted from the distinct character of such use-wear patterns.